The amazing book is not on fire : the world of Dan and Phil - Howell, Dan, 1991-; Lester, Phil, 1987- (London : Penguin Random House, Ebury Press, 2015)
YouTube stars Dan Howell and Phil Lester tell the humorous story of growing up, becoming YouTube stars, and give advice to their teen followers.
Keywords: Howell, Dan, -- 1991-; Lester, Phil, -- 1987-; Internet personalities -- England -- Biography; YouTube (Electronic resource); Radio broadcasters -- England -- Biography; JUVENILE NONFICTION / Humor / General; JUVENILE NONFICTION / Biography & Autobiography / Performing Arts; JUVENILE NONFICTION / Biography & Autobiography / General